Development and evaluation of a standardized research definition for opioid overdose outcomes - Binswanger, Ingrid A. (Subst Abus, 2019)
BACKGROUND: Increasing epidemiologic and intervention research is being conducted on opioid overdose, a serious and potentially fatal outcome. However, there is little consensus on how to verify opioid overdose outcomes for research purposes. To ensure reproducibility, minimize misclassification, and permit data harmonization across studies, standardized and consistent overdose definitions are needed. The aims were to develop a case criteria classification scheme based on information commonly available in medical records and to compare it to reviewing physician clinical impression and simple encounter documentation. METHODS: In two large health systems, we developed a case criteria classification scheme for opioid overdose based on prior literature, expert opinion, and pilot testing with sample medical records. We then identified emergency department and hospital encounters (n=259) with at least one International Classification of Diseases–9–Clinical Modification (ICD-9-CM) codes suggestive of a pharmaceutical opioid or heroin poisoning. Physicians conducted structured medical record reviews to identify the proposed case criteria and generate a clinical impression and trained abstractors verified documentation. We then compared the case criteria classification scheme to clinical impression and encounter documentation. RESULTS: We developed a quantitative opioid overdose case criteria classification scheme which included three sets of major criteria and nine minor criteria (supporting documentation). The confirmation rates of the ICD-9-CM codes using the case criteria classification scheme, clinical impression, and encounter documentation ranged from 50.4% to 52.7% at one site and 55.5% to 67.2% at the second site. Discrepancies across approaches and sites related to differences in available records and documentation of clinical signs of overdose. CONCLUSIONS: We propose a novel case criteria classification scheme for opioid overdose that could be used to rigorously and consistently define overdose across multiple research settings. However, prior to widespread use, further refinement and validation are needed.